Simulation-based education for nurse and midwife advanced practitioners: a scoping review - Eustace-Cook, Jessica; Mc Cabe, Catherine; Mc Tague, Karen (My University, 2025)
Simulation-based education (SBE) is widely adopted in undergraduate nurse and midwife education. The extent, format and evidence for its use in nurse and midwife advanced practitioner education is under explored. The aim of this scoping review was to establish the extent and types of available evidence on SBE for nurse and midwife advanced practitioner education.
PUBLISHED
Keywords: Simulation-based education (SBE); nurse and midwife; advanced practitioner education; Simulation-based education (SBE); nurse and midwife; advanced practitioner education; Telecommunications; Children's Nursing; Clinical learning environment in nursing; Innovation in learning; NURSING EDUCATION; Nursing Education; Other; Education